The male brain - Brizendine, Louann, 1952- (Broadway Books, 2010)
Dr. Louann Brizendine, the founder of the first clinic in the country to study gender differences in brain, behavior, and hormones, turns her attention to the male brain, showing how, through every phase of life, the "male reality" is fundamentally different from the female one.